Saskatchewan Paper : New works on paper by Saskatchewan Artists : A Community Programme Exhibition. (Regina, Sask. : Norman Mackenzie Art Gallery, University of Regina, 1980)
Cowin, Jack ; Cowley, Reta ; Fisher, Brian ; Knowles, Dorothy ; McKay, Arthur ; McVeigh, Don ; Nulf, Frank ; Perehudoff, William ; Ringness, Charles ; Rogers, Otto ; Thauberger, David ; Yuristy, Russell
Saskatchewan Paper : New works on paper by Saskatchewan Artists : A Community Programme Exhibition, Norman Mackenzie Art Gallery, University of Regina, Regina, 1980
boek
Keywords: Canada; Saskatchewan